Emocje jako składnik językowego obrazu gry komputerowej (na podstawie nazw emocji w recenzjach gier komputerowych) - Kaszewski, Krzysztof (Papers in Linguistics, 2019)
The aim of the article is to show how the emotion terms are used in reviews of computer games published in the media for video game enthusiasts: paper magazines and Internet portals. Analyses have shown that game reviewers are keen to use the emotion terms, most often indicating the groups: JOY, INTEREST, ANGER and BOREDOM. The emotions terms usually referred to the completely reviewed game, its content (fictional) and actions taken by the player, more often accompanying positive rather than negative assessments. Verbs (personal and non-personal forms – participles), nouns and adjectives were used to name emotions. The relationship was apparent between the nature of the computer game (entertainment, interactivity, symbolism) and the emotions being communicated.